Dork Diaries: OMG! All About Me Diary! - Russell, Rachel Renee (Simon & Schuster, Inc., 2013)
July 16:if you were going to be stranded on a desert island for two days, what three things would you bring with you [other than food and water]?
Keywords: Juvenile Fiction / Adventure